Clinical and genetic characterization of adult‐onset leukoencephalopathy with axonal spheroids and pigmented glia associated with CSF1R mutation. (29th September 2016) - Konno, T.; Yoshida, K.; Mizuno, T.; Kawarai, T.; Tada, M.; Nozaki, H.; Ikeda, S.‐I.; Nishizawa, M.; Onodera, O.; Wszolek, Z. K.; Ikeuchi, T.
Abstract : Background and purpose: The clinical characteristics of colony stimulating factor 1 receptor ( CSF1R) related adult‐onset leukoencephalopathy with axonal spheroids and pigmented glia (ALSP) have been only partially elucidated. Methods: Clinical data from CSF1R mutation carriers who had been seen at our institutions or reported elsewhere were collected and analysed using a specific investigation sheet to standardize the data. Results: In all, 122 cases from 90 families with CSF1R mutations were identified. The mean age of onset was 43 years (range 18–78 years), the mean age at death was 53 years (range 23–84 years) and the mean disease duration was 6.8 years (range 1–29 years). Women had a significantly younger age of onset than men (40 vs. 47 years, P = 0.0006, 95% confidence interval 3.158–11.177). There was an age‐dependent penetrance that was significantly different between the sexes ( P = 0.0013). Motor dysfunctions were the most frequent initial symptom in women whose diseases began in their 20s. Thinning of the corpus callosum, abnormal signalling in pyramidal tracts, diffusion‐restricted lesions and calcifications in the white matter were characteristic imaging findings of ALSP. The calcifications were more frequently reported in our case series than in the literature (54% vs. 3%). Seventy‐nine per cent of the mutations were located in the distal part of the tyrosine kinase domain of CSF1R (102 cases). There were no apparent phenotype−genotype correlations. Conclusions: The characteristics of ALSP were clarified. The phenotype of ALSP caused by CSF1R mutations is affected by sex.